2012
DOI: 10.1021/ml200261d
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of GNF-5837, a Selective TRK Inhibitor with Efficacy in Rodent Cancer Tumor Models

Abstract: Neurotrophins and their receptors (TRKs) play key roles in the development of the nervous system and the maintenance of the neural network. Accumulating evidence points to their role in malignant transformations, chemotaxis, metastasis, and survival signaling and may contribute to the pathogenesis of a variety of tumors of both neural and non-neural origin. By screening the GNF kinase collection, a series of novel oxindole inhibitors of TRKs were identified. Optimization led to the identification of GNF-5837 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 27 publications
4
81
0
Order By: Relevance
“…No examples were seen of TKDs that pack like Ror2, but close relatives of one of the TrkA crystallographic dimers were seen both in inhibitor-bound TrkC (PDB code 3V5Q [33]) and eight PDB entries describing structures of the inactive TKD from FGFR1. This crystallographic TrkA dimer is shown in Figure 5(A).…”
Section: Resultsmentioning
confidence: 99%
“…No examples were seen of TKDs that pack like Ror2, but close relatives of one of the TrkA crystallographic dimers were seen both in inhibitor-bound TrkC (PDB code 3V5Q [33]) and eight PDB entries describing structures of the inactive TKD from FGFR1. This crystallographic TrkA dimer is shown in Figure 5(A).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we also tested the role of Trk signaling in C5a-induced thermal hyperalgesia. Because of the lack of commercially available isoform-selective Trk inhibitors McCarthy and Walker, 2014), we used a potent pan-Trk inhibitor, GNF-5837 (Albaugh et al, 2012), in these experiments. As a positive control, we demonstrated that pretreatment with GNF-5837 inhibited NGF-induced thermal hyperalgesia (Fig.…”
Section: Ngf Plays a Critical Role In C5a-induced Thermal Hyperalgesiamentioning
confidence: 99%
“…GNF5837 is a family-selective tyrosine kinase inhibitor 52, while the tyrosine kinase activity of the trkA receptor can be inhibited by GW441756 (p IC 50= 8.7, 86) and tyrphostin AG879 76.…”
Section: Type VII Rtks: Neurotrophin Receptor/trk Familymentioning
confidence: 99%